PSYCHOLOGICAL IMPACT OF COVID 19 PANDEMIC ON DENTAL STUDENTS - Mudita Gupta, Vandana Gulia, Vineet Golchha*, Rahul Paul , Pooja Sharma,Deepti Yadav, Ish Sharma (Innovative Journal of Medical and Health Sciences, 2020)
Background : The coronavirus disease 2019 (COVID-19) which has spread rampantly to every country of the world. Dentists and dental students being amongst the professions with higher risks are under tremendous stress. Stress has been linked to serious side effects such as emotional exhaustion, anxiety, or depression. Therefore, our aim was to measure the levels of depression, anxiety and stress in dental students using the DASS-21 and to compare it with the sense of insecurity towards profession future due to Covid 19. Methodology: The data was collected through well-structured Google form from 1384 dental students studying in Delhi NCR. The entire form had two components. The first part of the form collected the demographic information of the students whereas the second part of questionnaire consisted of psychological evaluation using well established scale DASS 21. Result : The study showed 4% of the students with severe levels of depression,6% indicated severe level of anxiety, and 4% had severe stress. 87.2% of the students were insecure for their professional future due to spread of Covid19 and a significant correlation was found between future professional insecurity and depression, anxiety and stress Conclusion : High levels of depression, anxiety and stress was seen in undergraduate dental students which wass worsened by the current pandemic .There is a need to evolve with the current COVID 19 pandemic , impart confidence among them and find ways to decrease the levels of stress among these future dentists. Keywords: COVID19, Stress, dental students , DASS 21.